Immunosuppressants alter the immune response associated with Glucantime® treatment for Leishmania infantum infection in a mouse model - Bernardo, Lorena; Solana, Jose Carlos; Sánchez, Carmen; Torres, Ana; Reyes-Cruz, Eder Yaveth; Carrillo, Eugenia; Moreno, Javier (Frontiers in Immunology, 2023)
Background Immunosuppression is a major risk factor for the development of visceral leishmaniasis (VL). The number of patients receiving immunosuppressant drugs such as TNF antagonist (anti-TNF) and methotrexate (MTX) is increasing. In these patients, VL is more severe, their response to treatment poorer, and they are at higher risk of relapse, a consequence (largely) of the poor and inappropriate immune response they develop. Objectives To examine the effect of immunosuppressive treatment on the host immune response and thus gain insight into the reduced efficacy of pentavalent antimonials in these patients. Experiments were performed using BALB/c mice immunosuppressed with anti-TNF or MTX, infected with Leishmania infantum promastigotes, and then treated with Glucantime® at clinical doses. Results Immunosuppression with both agents impeded parasite elimination from the spleen and bone marrow. Low pro-inflammatory cytokine production by CD4+ and CD8+ T cells was detected, along with an increase in PD-1 and IL-10 expression by B and T cells in the immunosuppressed groups after treatment. Conclusion The immunosuppressed mice were unable to develop specific cellular immunity to the parasite, perhaps explaining the greater risk of VL relapse seen in pharmacologically immunosuppressed human patients.